1. x^{3/2}( - 1/ )

Made a attempt

x^{3/4}- x^{ 3/4}/x

= x^{3/2}. x^{1/2}- x^{3/2}/ (x^{1/2}. x^{3/2})

= x^{2}-x^{3/2}/x^{2}

= 1-x^{1/2}

Printable View

- June 2nd 2012, 03:15 PMzbest1966algebria expression
1. x

^{3/2}( - 1/ )

Made a attempt

x^{3/4}- x^{ 3/4}/x

= x^{3/2}. x^{1/2}- x^{3/2}/ (x^{1/2}. x^{3/2})

= x^{2}-x^{3/2}/x^{2}

= 1-x^{1/2} - June 2nd 2012, 03:34 PMPlatoRe: algebria expression
- June 2nd 2012, 04:32 PMWilmerRe: algebria expression
Hint: x^3/2) = xSQRT(x)

- June 2nd 2012, 04:43 PMReckonerRe: algebria expression
- June 2nd 2012, 04:56 PMPlatoRe: algebria expression
- June 2nd 2012, 07:10 PMWilmerRe: algebria expression
x*SQRT(x)*[SQRT(x) - 1/SQRT(x)]

= x^2 - x

= x(x - 1)

LATEX version in the near(?) future...